1998
DOI: 10.3354/meps162227
|View full text |Cite
|
Sign up to set email alerts
|

Effects of physical trawling disturbance in a previously unfished sheltered Scottish sea loch

Abstract: The effects of trawling disturbance on a benthic community were investigated with a manipulative field experiment in a fine muddy habitat that has been closed to fishing for over 25 yr. We examined the effects of extensive and repeated experimental trawl disturbance over an 18 mo period on benthic community structure and also followed the subsequent patterns of recovery over a further 18 mo During the penod of trawl disturbance the number of species and individuals increased and measures of diversity (Shannon'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
97
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(108 citation statements)
references
References 23 publications
9
97
0
2
Order By: Relevance
“…However, it is worth noting that several of the studies reported herein were undertaken in areas that have been closed to fishing (e.g. Tuck et al 1998, Bradshaw et al 2000, Sanchez et al 2000, or in areas that are known from fisheries-enforcement data to experience only limited or no fishing effort (Kaiser & Spencer 1996 or are known to have remained unexploited for reasons such as seabed obstructions (Ball et al 2000). In particular, those studies that have been undertaken in biogenic habitats are very likely to represent the true magnitude of the effects of fishing, as fishing by a commercial fleet would have removed the biogenic habitat and thereby eliminated the possibility of conducting experiments in such a habitat.…”
Section: Suitability Of Controls and Definition Of Recoverymentioning
confidence: 99%
“…However, it is worth noting that several of the studies reported herein were undertaken in areas that have been closed to fishing (e.g. Tuck et al 1998, Bradshaw et al 2000, Sanchez et al 2000, or in areas that are known from fisheries-enforcement data to experience only limited or no fishing effort (Kaiser & Spencer 1996 or are known to have remained unexploited for reasons such as seabed obstructions (Ball et al 2000). In particular, those studies that have been undertaken in biogenic habitats are very likely to represent the true magnitude of the effects of fishing, as fishing by a commercial fleet would have removed the biogenic habitat and thereby eliminated the possibility of conducting experiments in such a habitat.…”
Section: Suitability Of Controls and Definition Of Recoverymentioning
confidence: 99%
“…Furthermore, A C C E P T E D M A N U S C R I P T Rosenberg et al (2003) highlighted the presence of trawls tracks in both regions (southwestern and eastern) of the Gulf of Lions. Trawling is known to directly affect macrobenthic communities, leading to the loss of epifauna, the smoothing of sedimentary bed forms and the reduction of bottom roughness (Tuck et al, 1998).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thrush et al 1995, Jennings & Polunin 1996, Kaiser & Spencer 1996, Collie et al 1997, Engel & Kvitek 1998, Tuck et al 1998, Auster & Langton 1999, Ball et al 2000, Hall-Spencer & Moore 2000. However, the effects are less clear at broader scales and for chronic disturbances of the ocean bottom (Kaiser 1998(Kaiser , 2003.…”
Section: Introductionmentioning
confidence: 99%